Distribution of type VI secretion system (T6SS) in clinical Klebsiella pneumoniae strains from a Chinese hospital and its potential relationship with virulence and drug resistance. (January 2022) - Liao, Wenjian; Huang, Hai-hua; Huang, Qi-sen; Fang-Ling, Du; Dan Wei, Dan; La-Gen, Wan; Xiang, Tian-xin; Zhang, Wei; Liu, Yang
Abstract: Objectives: The type VI secretion system (T6SS) in Klebsiella pneumoniae strains isolated from the bloodstream, intestinal, the pyogenic liver abscess has been reported. Here we aimed to characterize T6SS in 248 Klebsiella pneumoniae isolates with all kinds of specimens from a Chinese hospital and to investigate the potential association of T6SS with virulence and drug resistance. Methods: T6SS genes, capsular serotyping genes, drug resistance genes, and virulence genes were identified by polymerase chain reaction (PCR). Antibiotic susceptibilities were examined by the disk diffusion method. To assess biofilm formation of these clinical Klebsiella pneumoniae isolates, 96-well microtiter plate assays were performed. MLST was used to analyze the genotypes of these Klebsiella pneumoniae isolates. Results: The frequency of T6SS genes among the clinical Klebsiella pneumoniae isolates was 72.2%. The T6SS-positive isolates displayed higher resistance to piperacillin-tazobactam, ciprofloxacin, levofloxacin, meropenem than the T6SS-negative isolates (P < 0.05). The T6SS-positive isolates formed significantly more biofilm mass than the T6SS-negative isolates (mean ± standard deviation [SD], 0.3 ± 0.09 vs.0.16 ± 0.06; P < 0.01). Compared to the T6SS-negative isolates, the T6SS-positive isolates had a higher frequency of virulence genes ( rmpA, fimH, entB, kfu, ybtS ) and the pLVPK-like plasmid (P < 0.05). Conclusion: In conclusion, the prevalence of the type VI secretion system is high in clinical Klebsiella pneumoniae isolates in a Chinese teaching hospital. T6SS-positive strains show higher biofilm-forming activity with high drug resistance and exhibit higher virulence potential. Highlights: We characterize T6SS  K.pneumoniae  isolates to investigate the potential association of T6SS with virulence and drug resistance. The prevalence of the type VI secretion system is high in clinical K.pneumoniae isolates in a Chinese teaching hospital. T6SS-positive strains show higher biofilm-forming activity with highly drug resistance and exhibit higher virulence.